Structure and morphology evolution in solid-phase synthesis lithium ion battery LiNi0.80Co0.15Al0.05O2 cathode materials with different micro-nano sizes of raw materials. Issue 8 (1st June 2018) - Xia, Shubiao; Liu, Jian-Jun; Li, Fushao; Cheng, Feixiang; Li, Xue; Sun, Chengke; Guo, Hong
Abstract: The LiNi0.80 Co0.15 Al0.05 O2 (NCA) cathode is endowed with a high energy density and excellent cycling performance. However, the preparation conditions for this material are quite harsh. Therefore, it is rather significant to obtain well-qualified NCA by simple solid-phase synthesis. In this study, the solid-phase synthesis of NCA cathode material is carried out by mixing two types of raw materials via stirring or sand milling. The effects of different particle sizes on the structure and morphology of NCA materials are analyzed. Owing to the different particle sizes of the raw materials, the diffusion path of Li + between the solid phases differs greatly. The XRD results show that the samples mixed by stirring have a worse cation mixture than those mixed by sand milling due to the larger particle size, smaller sintering surface energy, and insufficient sintering strength. The electrochemical results show that the sample mixed by sand milling has a higher specific capacity at a low rate, the initial discharge capacity is 199.22 mAh g −1, and the capacity retention rate is 86.9% after 50 cycles. In contrast, the initial discharge capacity of the sample mixed by stirring is 184.86 mAh g −1, and the capacity is 171.93 mAh g −1 after 50 cycles with a 93.0% capacity retention rate. Graphical abstract: Schematic of lithium ion diffusion during sintering fx1 Highlights: Structure and morphology evolution in the solid-phase synthesis NCA cathode. Thermal analysis and morphology evolution derived solid-phase reaction mechanism. Semi-in-situ analytical structure and Li + diffusion path. Taman theorem and XRD analysis deduced evolution of the solid state reaction.